Effect of Cost Benefit Analysis on Nigeria’s Civil Service: A Project Management Tool for Accelerating Human Settlement Action. - NWANKWO, Ajuluchukwu C.; EGBUNA, Onyinyechi K.; ALON, Anselem C. (Socialscientia: Journal of Social Sciences and Humanities, 2025)
By reducing the positive and negative impacts of a project to their equivalent money value, the Cost-Benefit Analysis determines whether on balance the project is worthwhile. The equivalent monetary value is based upon information derived from consumer and producer market choices; i.e., the demand and supply schedules for the goods and services affected by the project. Care must be taken to properly allow for such things as inflation. When all this has been considered, a worthwhile project is one for which the discounted value of the benefits exceeds the discounted value of the costs, i.e., the net benefits are positive. This is equivalent to the benefit/cost ratio being greater than one and the internal rate of return being greater than the cost of capital.